2011
DOI: 10.1371/journal.pone.0014558
|View full text |Cite
|
Sign up to set email alerts
|

Transient Alteration of Cellular Redox Buffering before Irradiation Triggers Apoptosis in Head and Neck Carcinoma Stem and Non-Stem Cells

Abstract: BackgroundHead and neck squamous cell carcinoma (HNSCC) is an aggressive and recurrent malignancy owing to intrinsic radioresistance and lack of induction of apoptosis. The major focus of this work was to design a transient glutathione depleting strategy during the course of irradiation of HNSCC in order to overcome their radioresistance associated with redox adaptation.Methodology/Principal FindingsTreatment of SQ20B cells with dimethylfumarate (DMF), a GSH-depleting agent, and L-Buthionine sulfoximine (BSO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 60 publications
1
40
0
Order By: Relevance
“…The cellular redox status can also be modulated by directly targeting glutathione. Glutathione depletion followed by radiotherapy results in large areas of apoptosis and significantly enhances the sensitivity of xenografted head and neck squamous cell carcinomas and non-small cell lung carcinomas to irradiation (87,88).…”
Section: Tumor Glucose Metabolism and Radioresistancementioning
confidence: 99%
“…The cellular redox status can also be modulated by directly targeting glutathione. Glutathione depletion followed by radiotherapy results in large areas of apoptosis and significantly enhances the sensitivity of xenografted head and neck squamous cell carcinomas and non-small cell lung carcinomas to irradiation (87,88).…”
Section: Tumor Glucose Metabolism and Radioresistancementioning
confidence: 99%
“…[76][77][78] Consequently, new strategies aimed to induce ROS via depletion of cellular glutathione can be viewed as promising therapeutic approaches against CSC. [79][80][81] Third lesson: Metabolism of amino acids and fatty acids…”
Section: Metabolism and Cancer Stemness: Lessons From Ips Cellsmentioning
confidence: 99%
“…However, several studies highlighted the role of activated JNK in apoptosis and tumor suppression in HNSCC. For example, Boivin et al (26) demonstrated that JNK mediates radiotherapy-induced apoptosis in human HNSCC cell lines, and Chen et al (46) demonstrated that the apoptotic effect of cisplatin and cordycepin act synergistically through the activation of the JNK/caspase-7/poly (ADP-ribose) polymerase signaling pathway in the human oral cancer cell line OC3. Furthermore, Noutomi et al (47) reported that JNK activation is involved in the molecular mechanism of tumor necrosis factor-related apoptosis-inducing ligand-induced cell death in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…c-Jun N-terminal kinases (JNKs) are members of the MAPK family, and become activated by a stressful cellular environment, including ultraviolet irradiation, oxidative stress, changes in osmolarity or metabolism, DNA damage, heat shock and inflammatory cytokine signaling (25). JNK signaling has been studied in HNSCC with controversial findings; thus, while certain studies support a pro-oncogenic function of JNK, others provide evidence that JNKs act as tumor suppressors in HNSCC (26)(27)(28).…”
Section: Jnk1/2 Expression and Modulation Of Stat3 Signaling In Oral mentioning
confidence: 99%